Does the “Generation of Freedom” Really Exist? Evidence from Qualitative Research among Polish and Ukrainian Students - Marzęcki, Radosław (Historia i Polityka, 2022)
Thirty years after the onset of democratisation in Central and Eastern Europe, the first generations of post-communist societies have been raised, educated and become professionally active. Objectively, they are a specific group of people whose primary and secondary socialisation occurred during a period that differed profoundly from that of their parents and older acquaintances. The article presents the results of a qualitative study conducted among Polish and Ukrainian students to diagnose their subjective generational self-identifications. The aim of the study was to determine whether and how young people in both countries perceive themselves and their social environment, and whether they identify themselves in terms of a unique generation.